2017
DOI: 10.1177/1010428317698366
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of long non-coding RNA identifies linc-RoR as a prognostic biomarker in oral cancer

Abstract: Oral squamous cell carcinoma is the most aggressive cancer that is associated with high recurrence, metastasis, and poor treatment outcome. Dysregulation of long non-coding RNAs has been shown to promote tumor growth and metastasis in several cancers. In this study, we investigated the expression of 11 selected long non-coding RNAs that are associated with cell proliferation, metastasis, and tumor suppression in oral squamous cell carcinomas and normal tissues by quantitative real-time polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 34 publications
0
73
0
Order By: Relevance
“…DE of HOTAIR has been assessed in six independent studies analysing 323 patients with results supporting its overexpression (Arunkumar, Deva Magendhra Rao et al., ; Fang et al., ; Lu et al., ; Wu & Xie, ; Wu et al., ; Zou et al., ). Conversely, the only study that examined HOTAIR expression in dysplastic lesions did not find significant DE (Gibb et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DE of HOTAIR has been assessed in six independent studies analysing 323 patients with results supporting its overexpression (Arunkumar, Deva Magendhra Rao et al., ; Fang et al., ; Lu et al., ; Wu & Xie, ; Wu et al., ; Zou et al., ). Conversely, the only study that examined HOTAIR expression in dysplastic lesions did not find significant DE (Gibb et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Three studies addressing TSCC (overall 159 patients) found significant overexpression (Fang et al., , ; Liang, Liang, Ouyang, Li, & Yi, ). When dealing with OSCC, two studies with similar sample size showed contrasting results, as only one was able to find significant DE (Arunkumar, Deva Magendhra Rao et al., ; Zhou et al., ). One report analysing The Cancer Genome Atlas (TCGA) data set found no significant DE neither for OSCC (15 cases) nor for TSCC (13 cases) (Zou et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for the imprinted maternally expressed lncRNA H19 is located on 11p15.5 in close proximity to insulin growth factor‐2 gene. Clinical data show contrasting evidence about H19 dysregulation in OSCC/TSCC (Arunkumar et al, ; Hong et al, ). When examining studies of OSCC/TSCC/HNSCC cell lines, this lncRNA is able to act as a sponge for more than one miRNA resulting in multiple axes promoting tumour cell migration and invasion.…”
Section: The Endogenous Rna Networkmentioning
confidence: 99%
“…In embryonic stem cells, gastric cancer cells and endometrial cancer stem cells, it acts as ceRNA to sponge miR‐145‐5p, favouring the expression of several core transcription factors (Arun et al, ; Wang, Xu et al, ; Zhou et al, ). In a cohort of 60 OSCC, it was observed that undifferentiated tumour samples overexpressing the LINC‐RoR also exhibited a significant downregulation of miR‐145‐5p and upregulation of the transcription factor Klf4 (Arunkumar et al, ). These results suggest that LINC‐RoR and maybe TUG1 overexpression might synergistically control miR‐145 function resulting in the upregulation of pluripotent transcription factors that regulate cellular differentiation (Arunkumar et al, ).…”
Section: The Endogenous Rna Networkmentioning
confidence: 99%
See 1 more Smart Citation